NECESSARY FACTORS OF ENSURING INFORMATION SECURITY IN YOUNG PEOPLE - Rakhimov Farukh Boltayevich; Habibullayev is the son of Farkhodbek Faizulla (Zeta Repository, 2023)
The article mentions the fact that information and communication and computer technologies have entered all aspects of our life today, and the basis of these changes is information, telecommunication and computer technologies, and the 21st century is the age of the information society. "Information is an important factor of socio-economic and cultural development.